Biomechanical interactions of different mini-plate fixations and maxilla advancements in the Le Fort I Osteotomy: a finite element analysis. Issue 16 (9th December 2016) - Huang, Shao-Fu; Lo, Lun-Jou; Lin, Chun-Li
Abstract: This study investigates the biomechanical interaction of different mini-plate fixation types (shapes/sizes and patterns) with segmental advancement levels on the Le Fort I osteotomy using the non-linear finite element (FE) approach. Nine models were generated under a standard 1-piece LeFort I osteotomy for advancement with 3, 6 and 9 mm distances and four mini-plates with three fixation patterns including LL, LI, and II patterns placed on the maxillae models by integrating computed tomography images and computer-aided design system. The axial and oblique occlusal forces were 250 N applied to each premolar/molar and 125 N applied at 30° inclination to the tooth long axis and from palatal to buccal, respectively. The relative micro-movement values between the two maxillary bone segments and maximum mini-plate stress increased obviously with maxilla advancement increment and the increasing trend can be fitted by exponential curve. The corresponding values in II mini-plate fixation presented apparently high values in all simulated cases. The mini-plate stress concentration locations were found at the bending regions to increase high fracture risk. The mini-plate yield strength can be mapped to a critical (limited) advancement for three types of fixations for safe consideration. This study concluded that L-shaped mini-plates with lateral fixation are recommended to provide better stability. The risk for mini-plate fracture and bone relapse increases when maxillary advancement is larger than a critical value of 5 mm in the Le Fort I osteotomy.